Strategi Implementasi Nilai-Nilai Budaya Organisasi di MIS Al Ihsan Mabar - Indri Sofia; Muhammad Irvan Marsya; Syifa Aliya Naflah; Tiwi Wulandari; Wardani W (Madani: Jurnal Ilmiah Multidisiplin, 2023)
The strategy and set of values, leadership style, vision and mission, and understandings that are shared by individuals from the organization and the thoughts that are proven by new individuals are referred to as organizational culture. the success of an organizational culture depends on the existence of a strategy that can be used as a basis for competitiveness. the purpose of this study is to find out how the strategy is carried out in implementing organizational cultural values. The method used is to use a qualitative descriptive research method where reference sources come from field observations and use references from the web such as Google Scholar and also other sources from the internet. Applying organizational cultural socialization within an organization, the existence of organizational cultural socialization will create cultural uniformity within the organization. Every thing that has a negative impact on students is expected to have a positive impact on students.